2010
DOI: 10.1088/0963-0252/19/2/025010
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term plasma phenomena in a HiPIMS discharge

Abstract: High power impulse magnetron sputtering (HiPIMS) is a plasma-based thin film deposition technique in which extremely high power pulses are applied to a conventional magnetron sputtering source. As a result, the plasma density in HiPIMS discharges is considerably increased up to 10 19 m −3 , about three orders of magnitude higher than that in conventional direct current magnetron sputtering (DCMS) discharges. Hence the vapour of the sputtered species becomes highly ionised, leading to remarkable improvement in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 141 publications
9
94
1
Order By: Relevance
“…4, reported deposition rates are given for various target materials based on the data from Helmersson et al 62 and Samuelsson et al 8 The most common explanation to the reduction in deposition rate stems from a work by Christie, 63 where back-attraction of metal ions to the target followed by selfsputtering causes a reduction in the amount of sputtered particles reaching the substrate. Controlling and optimizing the potential profile in the cathode region will, therefore, greatly affect the number of metal ions incident on the target surface, 64 which so far has not been fully explored. Gas rarefaction, which was discussed in the previous section, is also likely to affect the deposition rate in HiPIMS processes.…”
Section: Deposition Ratementioning
confidence: 99%
“…4, reported deposition rates are given for various target materials based on the data from Helmersson et al 62 and Samuelsson et al 8 The most common explanation to the reduction in deposition rate stems from a work by Christie, 63 where back-attraction of metal ions to the target followed by selfsputtering causes a reduction in the amount of sputtered particles reaching the substrate. Controlling and optimizing the potential profile in the cathode region will, therefore, greatly affect the number of metal ions incident on the target surface, 64 which so far has not been fully explored. Gas rarefaction, which was discussed in the previous section, is also likely to affect the deposition rate in HiPIMS processes.…”
Section: Deposition Ratementioning
confidence: 99%
“…Very little is known about the afterglow regime of the HiPIMS discharge, but from Langmuir probe measurements [33] it is found that a weak plasma can be sustained for several microseconds (> 10 µs) after pulse-off. It is therefore possible that the increased amplitude of the first peak of m Ar n as the pulse width increases is related to the fact that the plasma decays slower and thus the bulk plasma will contain more Ar m at the beginning of the next HiPIMS pulse.…”
Section: Effects Of Hipims Pulse Widthmentioning
confidence: 99%
“…Not surprisingly, HiPIMS plasma has been extensively studied using Langmuir probes. [19][20][21][22][23] Various levels of time resolution have been demonstrated for selected positions of the probe, mostly focusing on the interesting region above the racetrack. However, measurements generally lack the survey character that may allow us to gain greater insights.…”
Section: Emissive Probe Techniquesmentioning
confidence: 99%